Construção de um indicador sintético-sistêmico de desenvolvimento sustentável : Municípios do Estado do Espírito Santo - Canal, Fabiano Venturim (2012)
This study was motivated by the interest in creating a synthetic index of sustainable development that can also enable a systemic vision of the reality studied. By its synthetic nature and its systemic character, this index was entitled a "syntheticsystemic" indicator of sustainable development. The general aim of this study was to develop a synthetic-systemic indicator of sustainable development for the state of Espírito Santo. In order to achieve this goal, as a theoretical framework, we discussed the theme of sustainable development and its indicators, and spoke out about the importance of adding systemic approach to building a sustainable development indicator. About the methodology, based on the structure and indicators of "IDS-Brasil 2010 , as well as variables from "Ecologic Footprint and "ESI , we selected 24 primary indicators for this study, which were transformed to values between zero to one, creating a way to compare them. After this, were applied three methods for the aggregation of these variables: arithmetic average, multivariate analysis by principal components and factor analysis, in order to choose the more appropriate method for measuring sustainable development for the state of Espírito Santo. The procedure used to assess the significance of the found estimates was the inference, and factor analysis method was selected because it presented, on average, the best coefficient of determination (R²). Finally, the results obtained by factor analysis were analyzed from a systemic perspective, developing this way a synthetic-systemic indicator of sustainable development for the state of Espírito Santo. This dissertation was planned to build an index able to measure and indicate the points in need of actions to be taken for effective corporate, social, economic and environmental governance to the state of the Espírito Santo, as a way to achieve sustainable development